Whether to join EMS or not: Signalling and the membership - Pertti Haaparanta (Bank of Finland, 1990)
It is argued that if in a dynamic context a central bank wants to signal its commitment to non-inflationary policies an EMS membership makes its task easier by requiring less restrictive policies than if it stays outo Despite this depending on the initial beliefs of the public the central bank may not like to be an EMS member. It is also shown that the EMS membership has partial signalling value in that the public thinks that a central bank choosing EMS is non-inflationary with a higher probability than a bank staying outside.
URN:NBN:fi:bof-201807311794
Keywords: 330